Preclinical Ultrasound-Guided Photoacoustic Imaging of the Placenta in Normal and Pathologic Pregnancy. (16th October 2018) - Yamaleyeva, Liliya M.; Brosnihan, K. Bridget; Smith, Lane M.; Sun, Yao
Placental oxygenation varies throughout pregnancy. The detection of early changes in placental oxygenation as pregnancy progresses is important for early identification of preeclampsia or other complications. This invited commentary discusses a recent preclinical study on the application of 3-dimensional photoacoustic imaging (PAI) for assessment of regional variations in placental oxygenation and longitudinal analysis of differences in placental oxygenation throughout normal pregnancy and pregnancy associated with hypertension or placental insufficiency in mice. Three-dimensional PAI more accurately reflects oxygen saturation, hemoglobin concentrations, and changes in oxygen saturation in whole placenta compared to 2-dimensional imaging. These studies suggest that PAI is a sensitive tool to detect different levels of oxygen saturation in the placental and fetal vasculature in pathologic and normal pregnancy in mice.